REALISASI MANAJEMEN UNIT PELAYANAN BIMBINGAN DAN KONSELING (UPBK) PADA SEKOLAH MENENGAH PERTAMA (SMP) PERCONTOHAN DAN PENGEMBANG IMPLEMENTASI KURIKULUM 2013 DI KABUPATEN GOWA - Syaharuddin, Syaharuddin; Rezky, Amelia (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
The purpose of this research is to find out and analyze and trace: 1) The level of readiness of BK Teachers in the implementation of guidance and counseling services, 2) Implementation of guidance and counseling services, and 3) To find out the factors that affect the readiness of BK Teachers and the implementation of guidance and counseling services in order to realize the management of guidance and counseling in junior high school (SMP) pilot and developer of curriculum implementation 2013 in Gowa.The analysis used is the model